Kinerja Usaha Mikro Kecil dan Menengah (UMKM) Makanan Binaan Pusat Layanan Usaha Terpadu-Usaha Mikro Kecil dan Menengah (PLUT-UMKM) di Kota Bandar Lampung - Annajib, Askaruddin; Sayekti, Wuryaningsih Dwi; Riantini, Maya (Universitas Batanghari Jambi, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are productive businesses owned by individuals or legal entities that meet the requirements of a business. Micro- and small-sized businesses continue to confront a variety of financial and non-financial issues. Therefore, to encourage improved business performance, MSMEs are provided with coaching and/or mentoring by the Integrated Business Service Center-Micro, Small and Medium Enterprises (PLUT-UMKM). Most of the MSMEs assisted by PLUT-UMKM in Bandar Lampung City are food MSMEs. The focus of this study is to determine the achievement of PLUT-UMKM coaching targets, determine the performance of MSMEs, and analyze the effect of achieving PLUT-UMKM coaching targets on MSME performance. The method used in this research is a survey. The sampling technique in this study used proportional stratified random sampling. The data collection method used was interviews. This research employs quantitative descriptive analysis and multiple linear regression analysis to analyse the data. The results of this study indicate that the achievement of PLUT-UMKM coaching targets is in the good enough category, the performance of MSMEs assisted by PLUT-UMKM is in the good category, and the variables that have a significant effect on MSME performance are the variables of access to financing and business networks.